2011
DOI: 10.1093/mp/ssq077
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrosphingosine-Induced Programmed Cell Death in Tobacco BY-2 Cells Is Independent of H2O2 Production

Abstract: Sphinganine or dihydrosphingosine (d18:0, DHS), one of the most abundant free sphingoid Long Chain Base (LCB) in plants, has been recently shown to induce both cytosolic and nuclear calcium transient increases and a correlated Programmed Cell Death (PCD) in tobacco BY-2 cells. In this study, in order to get deeper insight into the LCB signaling pathway leading to cell death, the putative role of Reactive Oxygen Species (ROS) has been investigated. We show that DHS triggers a rapid dose-dependent production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 51 publications
4
30
0
Order By: Relevance
“…As previously shown, 8,10 external application of DHSinduced PCD in tobacco cells. The cell death ratio reached approximately 70% after a one hour treatment with 25 μM DHS (Fig.…”
Section: The No Production Is Not Required For the Dhs-induced Cell Dsupporting
confidence: 70%
See 2 more Smart Citations
“…As previously shown, 8,10 external application of DHSinduced PCD in tobacco cells. The cell death ratio reached approximately 70% after a one hour treatment with 25 μM DHS (Fig.…”
Section: The No Production Is Not Required For the Dhs-induced Cell Dsupporting
confidence: 70%
“…Co-treatment of cells with that H 2 O 2 generation is likely associated with basal defense mechanisms. 10 In the present study, we further investigated the DHS signaling cascade leading to cell death in tobacco BY-2 cells, by evaluating the involvement of another key signaling molecule i.e., nitric oxide (NO). In plants, NO is known to play important roles in numerous physiological processes including germination, root growth, stomatal closing and adapative response to biotic and abiotic stresses (reviewed in ref.…”
Section: Dhs Induces a Rapid No Production In Tobacco By-2 Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In tobacco plants the new PCD inducers such as ultraviolet B overexposure [25] and dihydrosphingosine [26] have been reported, recently. We hope the present results may also open a new gate towards the studies with regard to the MBP-induced cell death in a plant cell and its signaling pathways in the future.…”
Section: Abstract: Cell Death E Coli Maltose-binding Protein (Mbpmentioning
confidence: 99%
“…Plants also activate phenylpropanoid pathway and biosynthesis of antioxidant compounds during PCD induction [36]. However, a new report shown that dihydrosphingosine induces programmed cell death in tobacco cells independent of ROS [26].…”
Section: E8000s; New England Bio Lab)mentioning
confidence: 99%